STUDY ON VISUAL SCENARIOS FOR UNDERSTANDING POLITICAL SYSTEM OF THE GOND COMMUNITY OF NUAPADA DISTRICT IN ODISHA - Majhi, Hutasan; Kiro, Abinas (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This paper explores the political system of the Gond tribe in the Nuapada district of Odisha. The Gond tribe’s political structure is a significant component of the broader tribal polity within the state. This study examines the traditional governance mechanisms, leadership roles, and decision-making processes that characterize the Gonds’ political organization. By analyzing these aspects, the paper aims to provide insights into how the Gonds maintain social order, resolve conflicts, and preserve their cultural identity. Despite the influence of globalization and modern technology, the traditional ideologies and practices of the Gond community in the Boden block of Sunapur village also known as the oldest village practicing self-managed democracy remain intact. In the primitive and agrarian society of the Gond tribe in Nuapada district, governance is implemented by tribal chiefs and the Gond community Panchayati. In the Gond’s traditional political system, functions typically performed by modern states are carried out by social control mechanisms within the community. The rules and working procedures of these organizations, enforced by political institutions, sustain the social order. Here, the primary as well as the secondary source materials is methodologically utilized by the scholar.